Characteristics of cerebral hemodynamics assessed by CT perfusion in moyamoya disease. (January 2018) - Sasagawa, Ayaka; Mikami, Takeshi; Hirano, Toru; Akiyama, Yukinori; Mikuni, Nobuhiro
Highlights: The parameters on CT perfusion are useful for assessing hemodynamics. In moyamoya disease, the parameters of CT perfusion were characteristic. They might influence the occurrence of clinical symptoms or postoperative complications. Abstract: Due to the recent development of multidetector row computed tomography (CT), hemodynamic parameters can now be conveniently obtained with CT perfusion. The purpose of this study is to characterize the hemodynamic parameters of CT perfusion in moyamoya disease, and to discuss the differences in collateral circulation between moyamoya disease and atherosclerotic disease. A total of 16 hemispheric sides of 15 patients with moyamoya disease and 10 hemispheric sides of 9 patients with atherosclerotic disease who underwent bypass surgery were included. CT perfusion was performed with 123 I-IMP SPECT. Cerebral blood flow (CBF), cerebral blood volume (CBV), and mean transit time (MTT) values obtained by CT perfusion using standard singular value decomposition as the deconvolution algorithm in moyamoya disease were calculated. Preoperative values of these parameters were compared with those of atherosclerotic disease. Then, the postoperative changes of these parameters were analyzed. In the impaired side, CBF as measured by CT perfusion was correlated with that measured by 123 I-IMP SPECT. In moyamoya disease, CBV as measured by CT perfusion was significantly increased compared to in atherosclerotic disease, yet CBF was significantly decreased in atherosclerotic disease. Postoperatively, the asymmetry ratios of MTT were significantly improved, especially in atherosclerotic disease compared with moyamoya disease. On CT perfusion, the parameters included transit time and arrival time. CBV increase in moyamoya disease and postoperative improvement of MTT, especially in atherosclerotic disease, were unique characteristics in each. This might be due to the difference of collateral circulation and compensatory mechanisms between moyamoya disease and atherosclerotic disease.